Pengaruh Strategi Pemasaran Politik dan Niat Memilih terhadap Elektabilitas Calon Legislatif Kabupaten Probolinggo - Alfiana Firda Afnaini; Cosmas Gatot Haryono (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to analyze the influence of political marketing strategies and voting intention on the electability of legislative candidates in Probolinggo Regency. The study is motivated by the phenomenon that legislative candidates’ electability at the local level is shaped not only by the intensity of campaign activities, but also by social closeness and community-based relationships among voters. This research employed a quantitative approach with an explanatory design. Data were collected through a survey involving 204 respondents who participated in the 2024 Legislative Election and were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that political marketing strategies have a positive and significant effect on both voting intention and electability. In addition, voting intention also has a significant positive effect on electability. Furthermore, voting intention serves as a partial mediating variable in the relationship between political marketing strategies and electability. The findings indicate that electability is not solely influenced directly by political marketing strategies but is also shaped through the formation of voting intention within a relational social context among voters. This study contributes to the development of political marketing literature, particularly in explaining the formation of voting intention and electability in the context of local legislative elections.